Taxonomia das espécies brasileiras de Actinopus perty, 1983 (Araneae, Mygalomorphae, Actinopodidae) - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2009)
This work is divided into two chapters : "Chapter I - About the identity of the type species Actinopus tarsalis Perty , 1833 ( Araneae , Mygalomorphae , actinopodidae ) " and " Chapter II - Taxonomy of Brazilian Species of Actinopus Perty , 1833 ( Araneae , Mygalomorphae , actinopodidae ) " . This format was used to accelerate the publishing process necessary to validate the taxonomic changes proposed in the work . The first chapter is subject to immediate submission and has been formatted according to the rules of Iheringia magazine (Annex I) . The second chapter also formatted according to the rules of Iheringia magazine (Annex I) , shall be submitted after completion with the examination of the type of BMNH material.
Keywords: Aracnídeos; Actinopodidae; Actinopus tarsalis; Aranha; Taxonomia; Brasil - País; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES